Enforcement of Environmental Criminal Law Based on Ecological Justice: Green Criminology Analysis of Structural Crime in Indonesia - Wisnu Indra Cahaya; Fero Sanjaya; Herlita Eryke (UNIVERSITAS PAKUAN, 2026)
This study examines the implementation of environmental criminal law enforcement in Indonesia through the perspectives of green criminology and green victimology, focusing on the ongoing challenges in controlling ecological crimes and protecting environmental victims. The research uses an empirical sociological-legal approach, with a descriptive-analytical framework to analyze court decisions and field information from law enforcement officials and affected communities. The results show that environmental law enforcement in Indonesia still prioritizes administrative mechanisms over criminal sanctions, which are often applied inconsistently and selectively. This analysis reveals that such legal patterns weaken the deterrent effect, especially against corporate actors, and fail to uphold ecological justice because court decisions often ignore the environment as the primary victim and eliminate mandatory restoration. As a result, environmental damage is often treated as a formal violation rather than a serious structural crime. To address this issue, this paper recommends strengthening the use of criminal instruments for significant ecological violations, integrating mandatory environmental restoration into every court ruling, and increasing the participation of affected communities in legal processes to ensure comprehensive ecological restoration and social protection.